Prostaglandin E1 Dose and Duration as Determinants of Adverse Outcomes in Neonates with Duct-Dependent Congenital Heart Disease: A Systematic Review and Meta-Analysis - Dina Luthfiyah; Muhammad Ali Shodikin; Sri Lilijanti Widjaja (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Prostaglandin E1 (PGE1) infusion remains the cornerstone of medical stabilisation in neonates with duct-dependent critical congenital heart disease (DD-CCHD), yet contemporary guidance on optimal dose and duration is not informed by quantitative synthesis of recent evidence. Methods: A systematic review and meta-analysis were conducted in accordance with the PRISMA 2020 and MOOSE statements. PubMed/MEDLINE, ScienceDirect, OpenAlex and Europe PMC were searched (1st January 2014 – 30th April 2026) for original observational studies reporting PGE1 dose and/or duration with at least one adverse outcome in neonates (≤28 days) with DD-CCHD. The Newcastle–Ottawa Scale (NOS) and GRADE were applied. The primary outcome was the pooled prevalence of any PGE1-related adverse event using the Freeman–Tukey arcsine transformation under a DerSimonian–Laird random-effects model with the Hartung–Knapp–Sidik–Jonkman variance adjustment. The secondary, hypothesis-generating outcome was the pooled standardised mean difference (Hedges g) between higher- and lower-dose strata via the Chinn conversion. Heterogeneity, leave-one-out sensitivity, prespecified subgroup analyses, meta-regression and Egger regression were performed. Results: Ten observational studies enrolling 1,060 neonates were included. The pooled prevalence of any PGE1-related adverse event was 0.617 (95% confidence interval [CI] 0.509–0.724; I² = 87.6%). The secondary pooled Hedges g was 0.085 (95% CI −1.93 to 2.10), reflecting directional heterogeneity. Apnoea ranged from 9% to 52%, with a clear dose-related signal in two studies (relative risk approximately 1.97, p = 0.037; relative risk approximately 0.44, p = 0.015). Egger's intercept was 0.58 (p = 0.81), indicating no asymmetry. Meta-regression on median initial dose suggested dose-related apnoea risk. Conclusion: In neonates with DD-CCHD, approximately 62% experienced at least one PGE1-related adverse event. Initiation at 0.005–0.010 µg/kg/min should be regarded as the contemporary clinical default, with structured surveillance for apnoea and fever within 48 hours, gastrointestinal intolerance after 7–10 days and skeletal toxicity after 28 days.